AsteriskNOW : a practical guide for deploying and managing an Asterisk-based telephony system using the AsteriskNOW software appliance /: a practical guide for deploying and managing an Asterisk-based telephony system using the AsteriskNOW software appliance. (2008) - Unknown
No abstract available